Asymmetry of the Developing Brain, Structural Anomalies, and Genetic Variants in the Pathogenesis of Unilateral Spastic Cerebral Palsy (uCP), a Common Neurological Symptom in Intellectual Disability, is Discussed in the form of a Narrative Overview - Martin, Peter (Journal of Intellectual Disability - Diagnosis and Treatment, 2025)
Asymmetrical form and structural features of the brain can occur both as physiological hemispheric differences and as pathological left-right disparities. This review starts with findings on physiological brain development. It focuses primarily on non-physiological asymmetries between the left and right brain hemispheres and their impact on brain function, particularly motor functions. These are discussed in the context of cerebral palsy, specifically unilateral cerebral palsy, with a particular emphasis on genetic aspects. Pathogenic variants in specific genes can have diverse effects on structural brain development and, consequently, brain function. Several groups of genes must be distinguished based on their impact on the developing brain. These include variants in genes related to the coagulation system, angiogenesis, mitochondrial functions, and oxidative phosphorylation, which contribute to encephaloclastic lesions in the developing brain (e.g., periventricular or subcortical leukomalacia). These are distinct from gene variants that lead to disruptions in neuronal induction, proliferation, migration, aggregation, differentiation, and synaptic connectivity. Neurological symptoms, such as the development of spastic hemiparesis/cerebral palsy, can arise from genetically caused structural-functional disorders at both macroscopic (e.g., hemimegalencephaly) and microscopic levels (e.g., synaptic scaffolding). Additionally, disruptions in the structure and function of perineuronal networks must also be considered in this context. The ultimate goal of this review is to describe and discuss the pathways involved in the pathogenesis of unilateral cerebral palsy in a differentiated manner, with a particular focus on molecular genetic aspects.